Zarządzanie kosztami obsługi klienta i kanału dystrybucji w warunkach stosowania rachunku kosztów działań - Leszczyński, Zbigniew (Cost Management of Channel Distribution and Client in an Activity-Based Costing Environment, 2008)
The article presents the modeling of information connected with the profitability of channel distribution and client in an Activity-Based Costing Environment. It also presents the cost management method of channel distribution and client using information creations by ABC system.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 32, s. 58-67